Ideals of the form I1(XY). (March 2019) - Saha, Joydip; Sengupta, Indranath; Tripathi, Gaurab
Abstract: In this paper we compute Gröbner bases for determinantal ideals of the form I 1 ( X Y ), where X and Y are both matrices whose entries are indeterminates over a field K . We use the Gröbner basis structure to determine Betti numbers for such ideals.